Inactivation of Bacillus anthracis Spores during Laboratory-Scale Composting of Feedlot Cattle Manure - Xu, Shanwei; Harvey, Amanda; Barbieri, Ruth; Reuter, Tim; Stanford, Kim; Amoako, Kingsley K.; Selinger, Leonard B.; McAllister, Tim A. (Frontiers in Microbiology, 2016)
Anthrax outbreaks in livestock have social, economic and health implications, altering farmer’s livelihoods, impacting trade and posing a zoonotic risk. Our study investigated the survival of B. thuringiensis and B. anthracis spores sporulated at 15ºC, 20ºC or 37ºC, over 33 days of composting. Spores ( 7.5 log10 CFU g-1) were mixed with manure and composted in laboratory scale composters. After 15 days, the compost was mixed and returned to the composter for a second cycle. Temperatures peaked at 71°C on day 2 and remained ≥55°C for an average of 7 days in the first cycle, but did not exceed 55°C in the second. For B. thuringiensis, spores generated at 15°C and 21°C exhibited reduced (P < 0.05) viability of 2.7 and 2.6 log10 CFU g-1 respectively, as compared to a 0.6 log10 CFU g-1 reduction for those generated at 37°C. For B. anthracis, sporulation temperature did not impact spore survival as there was a 2.5, 2.2 and 2.8 log10 CFU g-1 reduction after composting for spores generated at 15°C, 21°C and 37°C, respectively. For both species, spore viability declined more rapidly (P < 0.05) in the first as compared to the second composting cycle. Our findings suggest that the duration of thermophilic exposure (≥55°C) is the main factor influencing survival of B. anthracis spores in compost. As sporulation temperature did not influence survival of B. anthracis, composting may lower the viability of spores associated with carcasses infected with B. anthracis over a range of sporulation temperatures.